Towards a psychosocial model of crowd behaviour - Mohd Mahudin, Nor Diana; Abdul Rahman, Shukran; Ahmad Hatta, Zulkarnain; Abdul Ghani, Noraida; Sulong, Jasni; Mohd Hashim, Intan Hashimah; Md Saad, Zarina (2016)
Among people who moved in large-scale gatherings of crowds, there are increased risks of injury and mortality from crushing, asphyxiation, and the spread of communicable diseases. The most compelling data come from the many incidents of human stampedes and disasters during sports events, music festivals, and religious gatherings. These incidents raise three important theoretical questions: (1) what are the possible components that make up “crowd behaviour”; (2) what are the different factors that affect how people behave in large crowds?; and, (3) how do these factors act and interact with crowd behaviour? Here, we proposed a conceptual model of psychosocial predictors of crowd behaviour, which attempts to address these questions by synthesising knowledge across several psychological, sociological, medical, computer science, and engineering literatures. This model maintains that crowd behaviour consists of three major dimensions: behaviour, affective, and cognitive; and these dimensions are influenced by nine corresponding factors: personality trait, familiarity of crowded situations, expectation of being crowded, leadership in the crowd, perception of crowd mood, types of the crowd, perception of lawlessness of the crowd, social atmosphere among the crowd, as well as the surrounding people's behaviours and emotions. This model offers an integrative framework for understanding the predictors and dimensions of crowd behaviour. The implications of this model are discussed in relation to research, practice, and policy.